2010
DOI: 10.3324/haematol.2009.016113
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive large B-cell lymphoma with plasma cell differentiation: immunohistochemical characterization of plasmablastic lymphoma and diffuse large B-cell lymphoma with partial plasmablastic phenotype

Abstract: The online version of this article has a Supplementary Appendix. BackgroundPlasmablastic lymphoma has recently come to be considered a distinct entity among mature B cell neoplasms, although the limits with diffuse large B-cell lymphoma (DLBCL) need to be more accurately defined. Design and MethodsHere we show the results of an immunohistochemical study of 35 cases of plasmablastic lymphoma compared with a set of 111 conventional DLBCLs . ResultsOur results demonstrate that the use of a limited combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 31 publications
6
109
1
Order By: Relevance
“…13 BLIMP1 and XBP1 are expressed in plasma cell neoplasias and aggressive lymphomas with plasmablastic differentiation but their distribution in small B-cell lymphomas has been less investigated. 43 We found a relatively high expression of these transcriptions factors in mantle cell lymphoma and both of them were significantly more common in SOX11-negative than in -positive tumors. The knockdown of SOX11 by shRNA in mantle cell lymphoma cell lines leads to a downregulation of PAX5 and a switch toward the terminal B-cell differentiation program with increased expression of BLIMP1 and XBP1.…”
Section: Discussionmentioning
confidence: 67%
“…13 BLIMP1 and XBP1 are expressed in plasma cell neoplasias and aggressive lymphomas with plasmablastic differentiation but their distribution in small B-cell lymphomas has been less investigated. 43 We found a relatively high expression of these transcriptions factors in mantle cell lymphoma and both of them were significantly more common in SOX11-negative than in -positive tumors. The knockdown of SOX11 by shRNA in mantle cell lymphoma cell lines leads to a downregulation of PAX5 and a switch toward the terminal B-cell differentiation program with increased expression of BLIMP1 and XBP1.…”
Section: Discussionmentioning
confidence: 67%
“…Cytologically, the cells have immunoblastic or sometimes plasmablastic features, but they exhibit a plasmacytic phenotype with the absence of CD20 and PAX5 and expression of CD38, CD138, and BLIMP1 (Figure 1). 52,53 These lymphomas include anaplastic lymphoma kinase (ALK)-positive large B-cell lymphoma, plasmablastic lymphoma (PBL), and the human herpesvirus 8-related primary effusion lymphoma and large B-cell lymphoma associated with multicentric Castleman disease. PBL and human herpesvirus 8-related lymphomas usually occur in patients with immunodeficiency, most often HIV, and the tumors cells are infected by EBV, but usually with a latency type 1.…”
Section: Diffuse Large B-cell Lymphomasmentioning
confidence: 99%
“…In that study, EBER+/CD30+ DLBCL patients had worse outcome than that in EBER+/CD30-DLBCL patients. Montes-Moreno et al demonstrated that the acquisition of a partial plasmablastic phenotype in DLBCL is associated with aggressive clinical behavior (13). Several groups showed that addition of the anti-CD20 monoclonal antibody, rituximab, to anthracycline-based chemotherapy has clearly improved survival outcomes in patients with DLBCL in different clinical settings (14).…”
Section: Discussionmentioning
confidence: 99%